2022
DOI: 10.1371/journal.pone.0268589
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different exercise training programs on the functional performance in fibrosing interstitial lung diseases: A randomized trial

Abstract: Objectives We aimed to compare the effects of different aerobic exercise training (ET) programs on respiratory performance, exercise capacity, and quality of life in fibrosing interstitial lung diseases (f-ILD). Methods A case-control study where 31 patients with f-ILD diagnosis based on chest high-resolution computed tomography were recruited from Main Alexandria University hospital-Egypt. Ten patients were randomly assigned for only lower limbs (LL) endurance training program, and 10 patients for upper lim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 44 publications
1
2
0
Order By: Relevance
“…The pulmonary symptom scores in our study using the CAT demonstrated a statistically significant reduction during the course of the study, which was consistent with prior studies that have demonstrated that pulmonary exercises are effective in improving quality of life and pulmonary symptom scores in patients with COPD, asthma, bronchiectasis, and restrictive lung diseases (Essam et al, 2022;Pehlivan et al, 2019;Renolleau-Courtois et al, 2014;Tarigan et al, 2020). Recently, a 5-week, randomized controlled study of 52 individuals with post-COVID-19-related dyspnea who received a respiratory exercise breathing program via tele-medicine reported significantly improved quality of life scores in those individuals who were in the intervention group (Okan et al, 2022).…”
Section: Discussionsupporting
confidence: 91%
“…The pulmonary symptom scores in our study using the CAT demonstrated a statistically significant reduction during the course of the study, which was consistent with prior studies that have demonstrated that pulmonary exercises are effective in improving quality of life and pulmonary symptom scores in patients with COPD, asthma, bronchiectasis, and restrictive lung diseases (Essam et al, 2022;Pehlivan et al, 2019;Renolleau-Courtois et al, 2014;Tarigan et al, 2020). Recently, a 5-week, randomized controlled study of 52 individuals with post-COVID-19-related dyspnea who received a respiratory exercise breathing program via tele-medicine reported significantly improved quality of life scores in those individuals who were in the intervention group (Okan et al, 2022).…”
Section: Discussionsupporting
confidence: 91%
“…In this study, participants walked 119 m further ( p < .001), and the pulmonary symptom scores decreased by 7.3 points ( p < .001) following the pulmonary rehabilitation intervention (Hockele et al, 2022). Other studies have also resported signficant improvements in exercise capacity as pulmonary symptoms decrease, following respiratory strengthening interventions in both obstructive and restrictive lung disease populations (Essam et al, 2022; Lu et al, 2020; Mota et al, 2007). Thus, as participant’s pulmonary symptoms decrease following a respiratory strengthening intervention, exercise capacity tends to improve.…”
Section: Discussionmentioning
confidence: 93%
“…On the other hand, Gloeckl et al proved that SF-36 mental components were significantly improved [36]. Improvements in QOL can be attributed to exercise-based pulmonary rehabilitation programs and its benefits, breathing control due to breathing, exercises, and overall fitness and wellness [48][49][50].…”
Section: Discussionmentioning
confidence: 99%